Comparison of nicotine chewing-gum and psychological treatments for dependent smokers. Issue 6238 (16th August 1980) - Raw, M; Jarvis, M J; Feyerabend, C; Russell, M A
Abstract : The results of using nicotine chewing-gum to treat dependent smokers attending a withdrawal clinic were compared with the results of psychological treatment. At one-year follow-up 26 (38%) out of 69 people who received nicotine gum were abstinent compared with seven (14%) out of 49 who received psychological treatment (p < 0.01). Abstinence was confirmed by the measurement of carboxyhaemoglobin concentrations or expired air carbon monoxide. Blood nicotine concentrations when patients used the gum averaged half the smoking values, and side effects were few. Addiction occurred in only two subjects. Thus nicotine chewing-gum is a useful aid to giving up smoking and is probably acceptable even for people with cardiovascular disease.